High volume distension injection (HVDI) for chronic mid-portion Achilles tendinopathy: A service evaluation of clinical outcomes - Samuel Edwards; Manoj Sivan (Journal of Orthopaedics, Trauma and Rehabilitation)
Purpose: High Volume Distension Injection (HVDI) is a treatment adjunct in chronic mid-portion Achilles tendinopathy. This study analysed whether HVDI is safe and effective in an outpatient clinic setting. Methods: Retrospective service evaluation of 18 participants over 18 months. Ultrasound-guided saline, corticosteroid and bupivacaine was injected to disrupt vasculo-neural ingrowth, with post-procedure eccentric exercises. Mean follow-up was 8 weeks. Outcomes used were Numeric rating Scale (NRS) of pain, tendon thickness and Modified Ohberg score (MOS) of neovascularisation measured on Ultrasound and Doppler imaging. Results: Mean reduction in NRS was 5.30 ± 2.53 ( P < 0.001). Mean tendon thickness reduction was 0.21 ± 0.17 cm ( P < 0.001). Median MOS improved from 2.00 ± 2.00 to 1.00 ± 3.00 ( P = 0.009). No complications occurred. 11 participants had successful primary HVDI, 3 responded to a second injection. Two non-responders were referred for surgery and two referred for alternative therapy by patient preference. Conclusion: Significant reduction in pain, tendon thickness and neovascularity was observed in 78% of patients. Recurrence in 39%. HVDI with eccentric training is safe and effective intervention in outpatient clinic setting.